2011
DOI: 10.1007/s11130-011-0262-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Baking and Boiling on the Nutritional and Antioxidant Properties of Sweet Potato [Ipomoea batatas (L.) Lam.] Cultivars

Abstract: The effects of baking and boiling on the nutritional and antioxidant properties of three sweet potato cultivars (Beniazuma, Koganesengan, Kotobuki) cultivated in Turkey were investigated. The samples were analyzed for proximate composition, total phenolic content, ascorbic acid, β-carotene, antiradical activity, and free sugars. The dry matter, protein, and starch contents of the sweet potatoes were significantly changed by the treatments while the ash and crude fiber contents did not differ as significantly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 29 publications
5
33
2
Order By: Relevance
“…Carotenoid content in sweetpotatoes largely varies depending on cultivar and growing environment; however our values appeared to be in the range of previously published data (Dincer, Karaoglan, Erden, Tetik, Topuz & Ozdemir, 2011) . It was noted that while Covington had the highest β-carotene ratio (approx.…”
Section: Carotenoidssupporting
confidence: 56%
“…Carotenoid content in sweetpotatoes largely varies depending on cultivar and growing environment; however our values appeared to be in the range of previously published data (Dincer, Karaoglan, Erden, Tetik, Topuz & Ozdemir, 2011) . It was noted that while Covington had the highest β-carotene ratio (approx.…”
Section: Carotenoidssupporting
confidence: 56%
“…After roasting, the average protein content was 7.90 g/100 g DW. These results were in accordance with the findings of Dincer et al (), who studied the nutritional and antioxidant properties of three sweet potato cultivars in Turkey. The results of this study showed that the protein content in the three types of fresh sweet potato was 4.3–5.1 g/100 g DW, and after boiling and baking, the protein content ranged from 4.4 to 5.0 g/100 g DW and 3.6 to 4.6 g/100 g DW, respectively.…”
Section: Resultssupporting
confidence: 93%
“…In contrast, concentrations of other antioxidant compounds, including vitamin C, were increased after both baking and boiling, and overall antioxidant capacity of sweet potato was increased after cooking [44]. However, after baking, the glycemic index of sweet potato was increased to 82, whereas after boiling it was only 41 (raw sweet potato has a glycemic index of 61).…”
Section: Vegetables and Antioxidantsmentioning
confidence: 94%